2007
DOI: 10.1007/0-387-32931-5
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of Intellectual and Developmental Disabilities

Abstract: A continuation Order Plan is available for this series. A continuation order will bring delivery of each new volume immediately upon publication. Volumes are billed only upon actual shipment. For further information please contact the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 1,032 publications
(1,389 reference statements)
0
1
0
Order By: Relevance
“…The second condition has to do with depth and breadth of coverage. A copious body of literature has been published on interventions at the individual, group, and school levels (e.g., Bray & Kehle, 2011;Esquivel, Lopez, & Nahari, 2007;Gutkin & Reynolds, 2009;Jacobson, Mulick, & Rojahn, 2007;James, Jurich, & Estes, 2001;Jurich & Estes, 2000;Martinez & Klopott, 2005;Peacock, Ervin, Daly, & Merrell, 2010;Shinn & Walker, 2010). This chapter will be able only to skim the surface of the vast extant literature and will direct readers to sources that deal with specific topics in greater depth.…”
Section: Framing the Chaptermentioning
confidence: 99%
“…The second condition has to do with depth and breadth of coverage. A copious body of literature has been published on interventions at the individual, group, and school levels (e.g., Bray & Kehle, 2011;Esquivel, Lopez, & Nahari, 2007;Gutkin & Reynolds, 2009;Jacobson, Mulick, & Rojahn, 2007;James, Jurich, & Estes, 2001;Jurich & Estes, 2000;Martinez & Klopott, 2005;Peacock, Ervin, Daly, & Merrell, 2010;Shinn & Walker, 2010). This chapter will be able only to skim the surface of the vast extant literature and will direct readers to sources that deal with specific topics in greater depth.…”
Section: Framing the Chaptermentioning
confidence: 99%
“…Gentile, Cowan, and Dixon [14] further note that they experience limitations in physical abilities, reduced life expectancy, and seizure disorders. Jacobson, Mulick, and Rojahn [15] contend that individuals with SID have a significantly higher mortality rate. The neurotypical population tends to live 15 years longer than individuals with SID, who have a mortality three times higher than that of the general population [15].…”
Section: Severe Intellectual Disabilitymentioning
confidence: 99%
“…Jacobson, Mulick, and Rojahn [15] contend that individuals with SID have a significantly higher mortality rate. The neurotypical population tends to live 15 years longer than individuals with SID, who have a mortality three times higher than that of the general population [15]. This is attributed to their decreased ability to care for themselves, generally inferior structures, and the higher prevalence of physical defects.…”
Section: Severe Intellectual Disabilitymentioning
confidence: 99%
“…Parental stress levels are dynamic and depend on various factors, including the developmental state and behavior of the child [4][5][6]. For example, parental stress levels, in general, are higher among parents of children with developmental disabilities than parents of typically developing children [7]. A recent study [8] showed that parents of children with neurodevelopmental disorders reported higher levels of parenting stress compared to children of typical development.…”
Section: Introductionmentioning
confidence: 99%